2019
DOI: 10.1007/s00392-019-01461-7
|View full text |Cite
|
Sign up to set email alerts
|

One year VARC-2-defined clinical outcomes after transcatheter aortic valve implantation with the SAPIEN 3

Abstract: AimsTo evaluate 1-year outcome after transcatheter aortic valve implantation (TAVI) using the SAPIEN 3 (S3) prosthesis with emphasis on the composite endpoints “clinical efficacy after 30 days” and “time-related valve safety” proposed by the updated Valve Academic Research Consortium (VARC-2).Methods and resultsFour hundred and two consecutive patients undergoing transfemoral TAVI with the S3 were enrolled. Mean age was 81 ± 6 years, 43% were female and median logistic EuroSCORE I was 12% [8–19]. Device succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The Abdelaziz et al group did a meta-analysis review with 5859 patients and reported a major vascular complication of 8.7% and 8.5% in the percutaneous vs cut down group respectively [ 8 ]. Pellegrini et al reported a major vascular complication rate of 8% [ 9 ]. Mach et al showed VARC-2 access complications occurred significantly more often in percutaneous group than the cut down group (20.4% vs 8.5%), and minor complications were significantly higher in the PC compared to cut-down (14.4% vs 2.5%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Abdelaziz et al group did a meta-analysis review with 5859 patients and reported a major vascular complication of 8.7% and 8.5% in the percutaneous vs cut down group respectively [ 8 ]. Pellegrini et al reported a major vascular complication rate of 8% [ 9 ]. Mach et al showed VARC-2 access complications occurred significantly more often in percutaneous group than the cut down group (20.4% vs 8.5%), and minor complications were significantly higher in the PC compared to cut-down (14.4% vs 2.5%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proven as a safe and effective alternative, TAVR is gaining popularity for severe AS. 7 albeit several serious complications, such as annular rupture, aortic dissection, coronary J o u r n a l P r e -p r o o f 6 obstruction, and valve embolization and migration. The latter having a higher incidence although curiously less commonly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Proved as a safe and effective alternative, the use of TAVR has been increasing in popularity for severe AS, 7 albeit several serious complications have occurred, such as annular rupture, aortic dissection, coronary obstruction, and valve embolization and migration, with the latter having a higher incidence, although, curiously, it has been less commonly addressed. 8 , 9 The TRAVEL (transcatheter heart valve embolization and migration) registry identified five predisposing factors for TVEM, including malpositioning (50.2%), manipulation (20%), postdilatation (5.9%), sizing error (5.1%), and fast-rate pacing failure (4.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic aortic stenosis (AS) is a life‐threatening condition were transcatheter aortic valve implantation (TAVI) offers similar beneficial long‐term treatment outcomes as surgical aortic valve replacement 1‐3 . However, long‐term mortality after TAVI remains high and 30% of patients suffer from serious complications or lack improvement of symptoms and quality of life 1 year after TAVI 4‐11 . Incomplete patient selection criteria and preoperative risk scoring systems may explain some of these cases of inefficiency 12‐15 …”
Section: Introductionmentioning
confidence: 99%